CHILEAN COMUNISTY PARTY AND THE PLOT OCCUPATION UNDER DICTAROSHIP: THE “FIGHTING” FOR HOUSING, 1980-1984 - Reyes Soriano, Jaime (Revista de Historia Social y de las Mentalidades, 2015)
A new historical re-construction about the plot  occupation in Santiago between 1980 to 1984  and the participation of the Communist Party are  proposed in this article. Going to the publications  of that period, both from the opposition and in  favor to the regime opinion, plus the documents of  the Party, expose the facts and the consequences  there were inside the political organization,  regarding to the failures and successes that these  invasions had into the private property. From  these actions, it is tried to explain that the plot  occupations and slum settlement building,  together to protests, the violence executed  by the masses in the neighborhoods and the  FrentePatriotico Manuel Rodriguez armed actions  were an important issue in the analysis of the  Party to determine in the plenary session in 1984  that there were enough conditions to establish the  dictatorship fall.
Keywords: Plot occupation; Camps; Chilean Communist Party; Military dictatorship